2005
DOI: 10.1111/j.1474-9726.2005.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivospectrofluorimetry reveals endogenous biomarkers that report healthspan and dietary restriction inCaenorhabditis elegans

Abstract: SummaryAutofluorescent lipofuscin and advanced glycation end-products (age pigments) accumulate with age across phyla, yet little is understood about their formation under physiological conditions and their specific contributions to the aging process. We used in vivo spectrofluorimetry to quantitate autofluorescence in wild-type Caenorhabditis elegans and longevity mutants disrupted for distinct aspects of the aging process. In wild-type animals, age pigments increase into adulthood, accumulating slowly during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
245
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(257 citation statements)
references
References 74 publications
11
245
0
1
Order By: Relevance
“…Finally, when wild-type siblings that aged differently -as evaluated by changes in their motility -were compared, it was found that the still mobile and youthful ones at day 11 of their life spans contained only 25% of the lipofuscin that was found in severely motility-impaired siblings of the same age. This implies that lipofuscin accumulation reflects biological rather than chronological age (Gerstbrein et al, 2005). The positive correlations between lipofuscin accumulation and hampered cellular function are in harmony with observations that chronic feeding of rats with green tea between the age of 12 and 19 months delays hippocampal accumulation of lipofuscin and improves learning and memory.…”
Section: Lysosomal Accumulation Of Lipofuscin and Its Influence Osupporting
confidence: 78%
“…Finally, when wild-type siblings that aged differently -as evaluated by changes in their motility -were compared, it was found that the still mobile and youthful ones at day 11 of their life spans contained only 25% of the lipofuscin that was found in severely motility-impaired siblings of the same age. This implies that lipofuscin accumulation reflects biological rather than chronological age (Gerstbrein et al, 2005). The positive correlations between lipofuscin accumulation and hampered cellular function are in harmony with observations that chronic feeding of rats with green tea between the age of 12 and 19 months delays hippocampal accumulation of lipofuscin and improves learning and memory.…”
Section: Lysosomal Accumulation Of Lipofuscin and Its Influence Osupporting
confidence: 78%
“…Previously, whole-genome transcriptional profiles of worm populations of varying ages were generated using DNA microarrays [8,9] A concept of interest is to use biomarkers of aging to predict the lifespan of individuals within a population with an identical age and sharing the same environment. Levels of lipofuscin, a pigment thought to correlate with physiological age, were found to predict the remaining lifespan of worms [14]. Golden et al performed DNA microarray analyses on individual worms, with the aim of discovering genes that vary stochastically amongst individuals within an age-matched population [15,16].…”
Section: Transcriptional Profiles Of Aging In C Elegansmentioning
confidence: 99%
“…These biomarkers include behavioral decline and tissue aging (8)(9)(10)(11). Aging of C. elegans is characterized by a progressive decline in locomotion, both in speed and coordination (9,10,12), and decreased defecation and pharyngeal pumping rate (8,9,13). Old nematodes, like old humans, show progressive tissue and organ deterioration: muscles, gonad, intestine, and connective tissues degenerate in aged worms (9)(10)(11).…”
mentioning
confidence: 99%